Determinan Perilaku Hidup Bersih dan Sehat Pada Siswa Sekolah Dasar Negeri - Titin Nasiatin; Irma Nurul Hadi (Faletehan Health Journal, 2019)
Clean Life And Healthy Behavior (CLHB) in schools is an effort to empower students, teachers, and community in the school environment to know, want and be able to help themselves in the field of health by implementing CLHB and play an active role in realizing healthy schools. The purpose of this research was to know the determinant to CLHB in elementary school students in Deringo Village Citangkil District Cilegon City Year 2019. Research design is cross sectional. The sample of this research is 107 students of grade 5, where taken using total sampling method. Primary data collection using questionnaires. Secondary data obtained from Citangkil Puskesmas and school. Based on research results obtained as much as 49.5% of students who perform CLHB less, 36, 4% have poor knowledge, 44.9% have a negative attitude, 42, 1% of students said that the teacher support were less and 43, 9% parents support were less. The results of analysis showed that there was a significant relationship between attitudes (pv=0.009), the teachers support (pv = 0,000) and the parents support (pv=0,000) with CLHB in elementary school students. Suggestions from this research are expected that the school can maximize the function of UKS and provide facilities and infrastructures that support CLHB of students.